Factors contributing to animal health risks: Implication for smallholder pig production in Vietnam - Nguyen Thi Thu Huyen; Lapar, Ma. Lucila; Ninh Xuan Trung; Pham Thi Toan (Kasetsart University, 2017)
In Vietnam, there are about four million households producing pigs of which more than half are producing at small scale, i.e., about one to two pigs per production cycle. One of the most critical constraints to pig production, especially for small scale, is the presence of animal disease. Many types of diseases have been reported by smallholder pig producers in Hung Yen such as diarrhea, pneumonia, fever, blue ear, head edema and pasteurellosis. The percentage of sick pigs is highest among piglets (27 percent), as compared with growing pigs and fatteners (five percent each). Diseases could lead to death of pigs, resulting in economic losses to the pig producers. Estimates of the cost of mortality in pig production in Hung Yen were about 3.3 million VND per household, accounting for about 13.6 percent of total income from pig production. Results of this study suggest that there are some practices that contribute to mitigating disease risk and those practices can be easily applied at small scale of pig production. These practices are related to applying a suitable production scale, isolating different age classes of pigs, designing pig houses and using specialized livestock farming tools and sanitation. The value of losses avoided from the above practices is estimated at 320.3 USD per household per year.